A Correlation Study Of Breast Milk Production Among Indonesia Mother : The Role Of Baby Formula Milk Feeding History 0-6 Months Old - Hurin'in, Nur Maziyah; Ferianto, Kusno; Marfuah, Yuani Siti; Shofiana (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: Continuity of breastfeeding can be influenced by social support from other people who interact with the mother so that the mother can feel physical and psychological comfort. The purpose was correlation between history beginning giving formula milk with breast milk production in Soko Tuban and Kendawangan Ketapang. Method: Cross sectional approach, correlational analytical research method . The population was all mother who has baby aged 0-6 months a total of 9 1 respondents , the sample is 74 respondents , the author used a simple random sampling technique. Data analysis using the contingency coefficient test. Result: The results show that the majority or 66.2% of babies aged 0-6 months were given formula milk, and less than half or 33.8% of babies aged 0-6 months were not given formula milk, the majority or 60.8% of mothers' breast milk production was not smoothly, and less than part or 39.2% of the mother's breast milk production was smooth and of the 49 babies who were given formula milk, more than part of 44 people (59.5%) were in the category of non-smooth milk production, while of the 25 babies who were not given formula milk less than half in the smooth breast milk production category as many as 24 people (32.4%). Discussion: From these two variables, after being tested statistically using the Contingency Coefficient test, a significance value = 0.000 < a(0.05) was obtained, which means that H 1 was accepted, so that there was a correlation between the initial history of giving formula milk and the mother's breast milk production with a strong level of correlation 0.639. Conlussion: Researchers advise the public, especially mothers who have babies aged 0-6 months, that families should take the time to search for information. and come to health workers in order to seek information about The importance of exclusive breastfeeding so that families can support breastfeeding mothers in providing exclusive breastfeeding .